Examining The Impact of Artificial Intelligence (AI) – Assisted Social Media Marketing in Improving the Effectiveness of SMES Business Performance in Indonesia - Nofirda, Fitri Ayu; Hastuti, Dwi (Akuntansi & Ekonomika, 2025)
Artificial Intelligence (AI) is seen as a key technology to support economic growth by offering opportunities for innovation and management efficiency. This study focuses on Artificial Intelligence-Supported Social Media Marketing (AISMM) as a strategy to overcome marketing challenges and improve the effectiveness of SMES business performance, with management effectiveness as a mediator. This study uses a quantitative and descriptive approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, involving 200 SMES actors in Indonesia as respondents. The results of the study show that AISMM and effective business management have a significant influence on improving SMES business performance. These findings provide theoretical and practical contributions, as well as being a reference for SMES actors in adopting AI-based digital transformation strategies.